2012
DOI: 10.2147/ijn.s28647
|View full text |Cite
|
Sign up to set email alerts
|

Titanium dioxide induces apoptotic cell death through reactive oxygen species-mediated Fas upregulation and Bax activation

Abstract: Background: Titanium dioxide (TiO 2 ) has been widely used in many areas, including biomedicine, cosmetics, and environmental engineering. Recently, it has become evident that some TiO 2 particles have a considerable cytotoxic effect in normal human cells. However, the molecular basis for the cytotoxicity of TiO 2 has yet to be defined. Methods and results:In this study, we demonstrated that combined treatment with TiO 2 nanoparticles sized less than 100 nm and ultraviolet A irradiation induces apoptotic cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…According to many authors [139, 140, 143, 144], the key role in the cell death induced by the UV-excited NPs of TiO 2 or ZnO is played by ROS. They are strong oxidants but also important agents modulating ROS-sensitive signaling pathways that lead to the cell death.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…According to many authors [139, 140, 143, 144], the key role in the cell death induced by the UV-excited NPs of TiO 2 or ZnO is played by ROS. They are strong oxidants but also important agents modulating ROS-sensitive signaling pathways that lead to the cell death.…”
Section: Reviewmentioning
confidence: 99%
“…Yoo et al [144] studied the ROS mediation in the induction of both intrinsic and extrinsic apoptotic pathways since ROS stimulate the increase of pro-apoptotic protein (Bax) and death ligand (FasL) levels, respectively. ROS induce apoptosis in tumor cells also by modification of the activity of mitogen-activated protein kinases (MAPKs; EC 2.7.11.24) [149] and of the nuclear factor kappa B (NF-κB) [150].…”
Section: Reviewmentioning
confidence: 99%
“…Authors dissected signaling events leading to similar outcome (apoptosis) and found a significant contribution of chemical composition in downstream signaling events. TiO 2 NPs were shown to induce cell death through ROS dependent extrinsic and intrinsic pathway in human lung fibroblast and breast epithelial cells (Yoo et al, 2012). Moreover, TiO 2 NPs induced cell death in BECs was shown to involve caspase 8/Bid pathway (Kang et al, 2009, Shi et al, 2010).…”
Section: 5 Nanomaterials and Cell Death Signalingmentioning
confidence: 99%
“…Likewise, the increased cytotoxicity shown by all nanoparticles in a dosedependent manner may be due to the leakage of cellular enzymes including lactate dehydrogenase through the damaged plasma membrane. Different factors like size, shape and composition of nanoparticles, internalization, metabolism and excretion by the tissue or cell type may account for the differential toxicity of nanoparticles (Yoo et al, 2012;Manke et al, 2013;Sadiq et al, 2015). Further research on particokinetics and cytokinetics is needed to understand the exact mechanism behind nanotoxicity at cellular and genetic level.…”
Section: Fig 2: Effect Of Metal Oxide Nanoparticles On Ldh Release Imentioning
confidence: 99%